Minimally Invasive Surgery for Resection of Parapharyngeal Space Tumors - Duek, Irit; Sviri, Gill E.; Billan, Salem; Gil, Ziv (Journal of Neurological Surgery Part B: Skull Base, 2018)
Background Surgical removal of parapharyngeal space tumors (PPST) poses challenges due to the complex anatomy of the region. PPSTs are routinely resected by a transcervical approach using blind finger dissection. Large PPSTs or those located high at the skull base, often require transmandibular or infratemporal fossa approaches, associated with considerable morbidity.Objective Here, we describe an approach for PPST removal that comprises transcervical endoscopic, with or without transoral robotic technique.Materials and Methods We retrospectively studied the demographic, clinical, surgical, and outcome data of 11 consecutive patients who underwent PPST excision between June 2013 and July 2017 at our center. Patients either underwent a transcervical endoscopic procedure (n = 4), a transoral robotic procedure (n = 2) or a combination of the two procedures (n = 5).Results Complete tumor excision was achieved in all cases, with no intra-, peri-, or postoperative complications. Final histopathologic findings demonstrated pleomorphic adenoma for seven patients, cavernous hemangioma for one patient, and malignant tumors for three patients. The average tumor size was 44.22 ± 31.9 cm3 (range: 7.5–111 cm3). At follow-up (range: 3–42 months), there was no evidence of recurrence.Conclusions The approach described provides improved visualization and safe vascular control with minimum tumor stress, preventing the need for blind finger dissection, and allowing complete tumor removal while minimizing tumor spillage, nerve injury, and blood loss, maintaining excellent cosmetic and functional results. This approach could be utilized for the removal of large benign PPST, or small PPST located high.
Keywords: parapharyngeal space; parapharyngeal space tumor; minimally invasive; transoral robotic surgery; da Vinci robot system